Influence of The 'Polish Deal' Tax Reform On The Taxation of Sole Proprietorships – A Case Study - Krzysztof DZIADEK; Beata STARZYNSKA (Communications of International Proceedings, 2023)
The aim of the article is to analyze changes in the scope of personal income tax introduced by the "Polish Deal" tax reform and assess the impact of these changes on the tax burden of sole proprietorships using the example of a selected company. The hypothesis adopted in the article is that the changes introduced by the Polish Deal in the context of income tax may influence taxpayers' decisions regarding the choice of taxation for sole proprietorships. During the research, a review of changes in the rules for calculating health insurance contributions and personal income tax after January 1, 2022 (Polish Deal) and after July 1, 2022 (Polish Deal 2.0) was conducted. Subsequently, the tax burdens and components of the "MB-PROJEKT" company for the years 2020-2021 were analyzed, which settled its income tax as a linear tax of 19%. In addition, an assessment of tax burdens for alternative forms of taxation (progressive tax scale, lump-sum tax on recorded revenue) was carried out, taking into account the effective tax burden rate. The research results confirm that the "Polish Deal" contributed to an increase in tax burdens. From the perspective of sole proprietorships, the most significant impact on the increase in burdens was the change in the rules for determining the health insurance contribution and the inability to deduct the health insurance contribution from the tax. Comparative analysis of taxation forms indicates that the legislator favors the lump-sum tax on recorded revenue to a greater extent, which allows for the use of a preferential method of determining the health insurance contribution.
Keywords: tax reform; Polish Order; PIT; income tax; health insurance contribution; sole proprietorship